Challenges in the calibration of large-scale ordinary differential equation models. Issue 26 (2019) - Kapfer, Eva-Maria; Stapor, Paul; Hasenauer, Jan
Abstract: Mathematical models based on ordinary differential equations have been employed with great success to study complex biological systems. With soaring data availability, more and more models of increasing size are being developed. When working with these large-scale models, several challenges arise, such as high computation times or poor identifiability of model parameters. In this work, we review and illustrate the most common challenges using a published model of cellular metabolism. We summarize currently available methods to deal with some of these challenges while focusing on reproducibility and reusability of models, efficient and robust model simulation and parameter estimation.